Comparison of Multiple Needle Aspirations and Open Surgical Drainage in Management of Breast Abscess - Wasim Iqbal Sheih, Mudassar Suleri, Mazia Kulsoom (Journal of Rawalpindi Medical College, 2009)
Background: The treatment of breast abscess is a clinical dilemma which ranges from conservative treatment to surgical intervention. A recently highlighted approach is drainage of pus by needle aspiration under antibiotic cover with or without radiological guidance. This approach has advantages of complete resolution without scar formation and patient can continue breast feeding.. Methods: In this interventional study , 60 breast abscess cases , drained through needle aspiration ( Group A) or open surgical drainage ( Group B) were included. Results: Their age ranged from 16 to 40 year with peak age group between 20 to 30 year. 39 patients (65%) were lactating and 21(35%) were non-lactating at the time of presentation. All patients completed the follow up. There was complete resolution of symptoms in all patients however time resolution was significantly less in aspiration group (5 to 10 days) as compared with surgical drainage (12-30 days). There were 5 (16.6%) patients in aspiration group who required conversion to open surgical drainage after 4 aspirations. Among these patients 4 (80%) had abscess size greater than 5 cm and presented more than 5 days after the onset of symptoms. Conclusion: Needle aspiration is an effective alternative to open surgical drainage of breast abscess. The abscess which present early with a small size respond well to needle aspiration whereas most of the larger abscess presenting late require conventional surgical drainage.